Anthodiscus chocoensis Prance, Forest Specie in Critical Danger of Extinction in Costa Rica - Chinchilla Mora, Orlando (2016)
The article presents the main results for Anthodiscus chocoensis achieved by the project “Conservation of endangered forest tree species”. This project was developed between 2011 and 2013 by three Costa Rican public universities: UNA, ITCR and UNED.   The field survey confirmed that this species has a very low effective natural range, which covers only 3% of the country.  One third of its natural habitat is legally protected, representing only 1% of the national territory. This species is usually found in small remaining forested areas, often unconnected, existing in the lowlands of central and southern Pacific region.  In its natural habitat is scarce, because its populations are naturally conformed mainly by scattered trees and due to its commercial exploitation.  Current populations are composed of few and dispersed mature trees, with little presence of saplings and seedlings in the lower strata and the forest floor. The tree crown reaches the upper canopy, being a heliofita species at maturity. Environmental conditions that require juveniles remain uncertain, but field observations suggest that the seedlings do not survive in conditions of dense forest with low light intensity at ground level. Better germination and seedling survival was observed in small clearings within the forest that permits some more light intensity.  However, it was no observed saplings or seedling at the outside edge of the forest and nearby open field areas with high light intensity.  Flowering occurs mostly between the months of March to May, simultaneously with the production of new leaves. The fruits contain 12 capsules and generally have between 6 and 12 seeds (one per capsule), which remain inside the fruit during germination in nature.   At field and greenhouse levels, it has been observed that only one seed per fruit germinates. The causes of this are unknown.  Under greenhouse conditions, located at 1240 masl, germination was slow, irregular and low, taking between six months and 18 months, yielding seedlings in no more than 15% of the fruits.  The growth of seedlings in the greenhouse was also slow, reached an average height of 27 cm at 9 months, for a sample of 20 seedlings. The smallness of the remaining populations and habitat available, the low abundance of the species in the forest, the possible genetic erosion and the apparent low rate of natural reproduction, suggest a high possibility that the species is critically endangered and their populations could be below the “minimum viable size.” It is necessary to make detailed studies on the reproductive biology and population dynamics of this species, as well as on the genetic variation and endogamic levels that it presents in the forested islands that inhabits, in order to define an appropriate conservation strategy.  It is also necessary to develop techniques that will enable its ex situ reproduction and conservation.